2000
DOI: 10.3171/jns.2000.93.6.1003
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-guided resection of glioblastoma multiforme utilizing 5-ALA-induced porphyrins: a prospective study in 52 consecutive patients

Abstract: The observations in this study indicate the usefulness of 5-ALA-induced tumor fluorescence for guiding tumor resection. The completeness of resection, as determined intraoperatively from residual tissue fluorescence, was related to postoperative MR imaging findings and to survival in patients suffering from GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
611
5
12

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 812 publications
(644 citation statements)
references
References 43 publications
16
611
5
12
Order By: Relevance
“…Whether applying a lower ALA dose contributed to significant advantages over a higher ALA dose could be argued. The adverse effects regarding skin photosensitivity reported in the studies by other groups on adult patients has been few (< 1%) [16][17][18] and even though the severity of the adverse effects was reported to be transient, absence of PpIX fluorescence in the skin of patients is considered an advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether applying a lower ALA dose contributed to significant advantages over a higher ALA dose could be argued. The adverse effects regarding skin photosensitivity reported in the studies by other groups on adult patients has been few (< 1%) [16][17][18] and even though the severity of the adverse effects was reported to be transient, absence of PpIX fluorescence in the skin of patients is considered an advantage.…”
Section: Discussionmentioning
confidence: 99%
“…As the skin photosensitivity is the major adverse effect reported [16][17][18], fluorescence intensities in the skin of the patients were compared between the two ALA dose groups. To examine the skin photosensitivity, fluorescence of the skin was measured using the same fluorescence spectroscopy system and the same settings (10 mW, 0.4 s) with an identical fiberoptic probe which was previously cleaned and disinfected.…”
Section: Spectroscopy System and Measurementsmentioning
confidence: 99%
“…A prospective series on 52 patients published in 2000 showed that ALA-guided FGR was sensitive, specific, and resulted in gross total resection in 63% of patients [36]. Another similar prospective study on 114 consecutive intracranial lesions found a sensitivity between 83-87% and a complete resection rate of 77% [37].…”
Section: Other Studies Investigating Fluorescence-guided Resection: 5mentioning
confidence: 97%
“…As already shown by various groups, the administration of 5-aminolevulinic acid (5-ALA) leads to a highly selective accumulation of protoporphyrin IX (PpIX) in high-grade malignant gliomas. [22][23][24] A tumor-related deficient blood brain barrier and an altered activity level of several enzymes including ferrochelatase, which catalyzes the conversion of PpIX to heme, are central reasons for this phenomenon. [25] Tumor recognition with 5-ALA-induced PpIX is already effectively used for fluorescence-guided resection of malignant gliomas using surgical microscopes [22,23,26] or fiber optical probes [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] A tumor-related deficient blood brain barrier and an altered activity level of several enzymes including ferrochelatase, which catalyzes the conversion of PpIX to heme, are central reasons for this phenomenon. [25] Tumor recognition with 5-ALA-induced PpIX is already effectively used for fluorescence-guided resection of malignant gliomas using surgical microscopes [22,23,26] or fiber optical probes [27,28]. It leads to a significantly increased complete resection rate of these diffusely growing tumors and to a significantly enhanced progression-free survival rate after 6 months, translating into a progression-free survival prolongation of 1.5 months as compared to conventional white light resection.…”
Section: Introductionmentioning
confidence: 99%